Effect of Oatmeal on TNF-alfa of Blood of White Rats Exposed to Motor Vehicles Fumes - Sukma Sahadewa; Fara Disa Durry; Zulfan Febriawan; I Putu Agus Aris Wijaya Kusuma (Universitas Wijaya Kusuma Surabaya, 2024)
Background: Air pollution due to motor vehicle emissions causes several serious health problems including respiratory problems. Fumes exposure activated alveolar macrophages and epithelial cells release mediators such as LTB4, TNF-α, and IL-8. TNF-α are known induced acute inflammation and tissue damage. Oats are plant with high dietary fiber content and nutritional value. Oats are contain of antioxidant compounds source such as tocopherols and avenanthramides. Therefore, this research aims to determine the effect of oatmeal on TNF-α of white rats exposed to motor vehicle fumes. Methods: This research used true experiment design with Randomized Post-Test Only Control Group design using 16 white male rats divided into three groups: control group only was given standard fed (K1), second group was given standard fed and exposed with motor vehicle fumes (K2), third group was given standard fed mixed with 10 gr of oatmeal and exposed with motor vehicle fumes (K3) for ten days. After ten days of the treatment, blood of white rats from all groups will be taken intracardial then measured TNF- α levels. Results: Statistical test analyzed using SPSS Software 23. Oatmeal has an effect to decrease TNF-α levels (P<0.001). Conclusion: This study conclude that oatmeal can help reduce TNF-α levels when exposed to motor vehicle fumes.